IDENTIFIKASI PIGMEN KAROTENOID PADA BAKTERI SIMBION RUMPUT LAUT Kappahycus alvarezii - Sahara, Fera Nur Idawati; Radjasa, Ocky Karna; Supriyantini, Endang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Carotenoid is one of the most important pigments that have important roles for human health. Carotenoids are believed to improve the better immune responses, anticancer, antioxidant, provitamin A and are also used in the treatment of disease that are sensitive to light. Carotenoids are yellow pigments, orange to red pigments and usually found in vegetables and fruits, and are also found in animals, humans, fungi and bacteria. The aims of study were to analyze carotenoid pigments from bacterial symbionts from seaweed Kappaphycus alvarezii and to identify bacterial symbionts that produce carotenoid pigments. Pigment analysis was performed by a UV-VIS spectrophotometer and High Performance Liquid Chromatography (HPLC). Bacterial identification was performed based on biochemical tests. These results showed that from 12 bacterial symbionts isolated, there were 2 isolates that positively synthesize carotenoids pigments, ECJ K and ECJ OR bacteria. ECJ K bacterium contained of Violaxanthin and Î±-carotene pigments. While ECJ OR bacterium contained of Diadinoxanthin, Neoxanthin, Î³-carotene, Î²-carotene and Î±-carotene pigments. Bacterial identification showed that ECJ K bacterium was Brevibacterium maris and ECJ OR bacterium was Micrococcus varians. This result showed that bacterial symbionts of seaweed Kappaphycus alvarezii contained various pigments including in carotenoid pigments.